Ten years of the European Employment Strategy (EES) (Office for Official Publications of the European Communities, 2007)
Since its launch in 1997, the European Employment Strategy (EES) has played a central role in coordinating the EU's policies in order to create improved work for all. Its role has been underscored by the European Council on many occasions and it has become an essential tool to respond to one of EU citizens' main preoccupations: more and better jobs. The EES is designed to give direction to and ensure co-ordination of the employment policy priorities to which Member States subscribe at EU level. Heads of State and Government agreed on a framework for action around common objectives and employment policy priorities. This co-ordination of national employment policies at EU level is built around an annual process laid down in the EU Treaty revision of 1998, which was integrated in a renewable three-year cycle since the re-launch of the Lisbon Strategy in 2005.